The influence of resting heart rate on pulse wave velocity measurement is mediated by blood pressure and depends on aortic stiffness levels: insights from the Corinthia study - Papaioannou, Theodore G; Oikonomou, Evangelos; Lazaros, George; Christoforatou, Evangelia; Vogiatzi, Georgia; Tsalamandris, Sotiris; Chasikidis, Christos; Kalambogias, Aimilios; Mystakidi, Vasiliki-Xara; Galiatsatos, Nikolaos; Santouri, Mina; Latsios, George; et al. (Physiological measurement, 2019)
Objective: Increased resting heart rate as well as increased arterial stiffness are both independent predictors of cardiovascular events and mortality. Results of previous studies have failed to converge concerning the association between heart rate and arterial stiffness, regardless of other potential confounders, such as age, gender and particularly blood pressure (BP). We aimed to investigate: (a) the degree of association (if any) between resting heart rate and carotid-to-femoral pulse wave velocity (PWV), the gold standard index of arterial stiffness, (b) if the relationship between heart rate and PWV is mediated by BP levels and (c) whether their association is affected by the levels of aortic stiffening. Approach: Demographic, hemodynamic, laboratory and clinical data of 1566 subjects from the cross-sectional observational 'Corinthia' study were analyzed using univariate and multivariate regression models. Mediation analysis was performed to test whether mean arterial pressure (MAP) is a significant mediator in the heart rate-PWV relationship. The total population was divided in two groups of low and high arterial stiffness according to the median PWV value (8.6 m s−1). Main results: We found that (i) there is a significant association between heart rate and PWV, regardless of other confounding factors. An increase in heart rate by 20 b.p.m. can increase PWV by 0.5 m s−1. However, this association was significant only for subjects with increased aortic stiffness (PWV  >  8.6 m s−1) and not for those with PWV     8.6 m s−1. Further, (ii) heart rate-PWV association was partially mediated by MAP. Significance: Increased resting heart rate is related to increased aortic stiffness, only in subjects with stiffer aortas, regardless of BP and other risk factors and subjects' characteristics. The synergistic prognostic effect of increased arterial stiffness and elevated heart rate on target organ damage, cardiovascular events and mortality should be explored in future studies.